A Reliable Broadcast Protocol in Vehicular Ad Hoc Networks. (30th August 2015) - Fan, Xiumei; Wang, Chao; Yu, Jiguo; Xing, Kai; Chen, Yingwen; Liang, Jiawei
Periodical broadcasts of individual vehicle's safety information such as velocity and acceleration are critical in vehicular ad hoc networks (VANETs). However, current contention-based media access control (MAC) protocols cannot guarantee high performance in high density VANETs. In this paper, we propose a MAC protocol based on s -disjunct code to achieve reliable and real-time broadcasts via assigning a channel to each vehicle as the vehicle enters the network. Our protocol is adaptive as vehicles are required to adjust their communication ranges according to the network density in order to avert the interference among them. We conduct an extensive simulation study, and our results indicate that the proposed scheme can successfully achieve the requirements of the dedicated short range communication (DSRC) standard, that is, to broadcast safety information 10 times per second. Even at a high vehicle density, our scheme still guarantees that the success rates of both transmission and reception are greater than 95%, and the collision rates of access collision and merging collision are lower than 10 collisions/period.